Codon-optimized TDP-43 mediates neurodegeneration in a Drosophila model of ALS/FTLD - Yusuff, Tanzeen; Chang, Ya-Chu; Sang, Tzu-Kang; Jackson, George R.; Chatterjee, Shreyasi (Frontiers in Genetics, 2023)
Transactive response DNA binding protein-43 (TDP-43) is known to mediate neurodegeneration associated with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). The exact mechanism by which TDP-43 exerts toxicity in the brains, spinal cord, and lower motor neurons of affected patients remains unclear. In a novel Drosophila melanogaster model, we report gain-of-function phenotypes due to misexpression of insect codon-optimized version of human wild-type TDP-43 (CO-TDP-43) using both the binary GAL4/UAS system and direct promoter fusion constructs. The CO-TDP-43 model showed robust tissue specific phenotypes in the adult eye, wing, and bristles in the notum. Compared to non-codon optimized transgenic flies, the CO-TDP-43 flies produced increased amount of high molecular weight protein, exhibited pathogenic phenotypes, and showed cytoplasmic aggregation with both nuclear and cytoplasmic expression of TDP-43. Further characterization of the adult retina showed a disruption in the morphology and function of the photoreceptor neurons with the presence of acidic vacuoles that are characteristic of autophagy. Based on our observations, we propose that TDP-43 has the propensity to form toxic protein aggregates via a gain-of-function mechanism, and such toxic overload leads to activation of protein degradation pathways such as autophagy. The novel codon optimized TDP-43 model is an excellent resource that could be used in genetic screens to identify and better understand the exact disease mechanism of TDP-43 proteinopathies and find potential therapeutic targets.